Enhancing research impact through bibliometric analysis / Siti Hawa Shuid and Norhidayah Ismail - Shuid, Siti Hawa; Ismail, Norhidayah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Faculty of Accountancy, UiTM Cawangan Negeri Sembilan, Kampus Seremban, organised a workshop titled "Bengkel Gerak Gempur Penerbitan Jurnal Berindeks: Penulisan Bibliometric Analysis" on 5 February 2025. The workshop, a collaborative program with Perpustakaan Tun Abdul Razak, features En. Syaiful Hisyam Saleh, a librarian with extensive expertise in bibliometric analysis. His talk provided invaluable insights into effective research strategies for publishing in high-impact journals. Key Insights from the Workshop En. Syaiful emphasized several crucial strategies for researchers looking to enhance their bibliometric analysis.